2013
DOI: 10.1371/journal.pone.0058367
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptation to Chronic Inhibition of Mitochondrial Protein Synthesis in Acute Myeloid Leukemia Cells

Abstract: Recently, we demonstrated that the anti-bacterial agent tigecycline preferentially induces death in leukemia cells through the inhibition of mitochondrial protein synthesis. Here, we sought to understand mechanisms of resistance to tigecycline by establishing a leukemia cell line resistant to the drug. TEX leukemia cells were treated with increasing concentrations of tigecycline over 4 months and a population of cells resistant to tigecycline (RTEX+TIG) was selected. Compared to wild type cells, RTEX+TIG cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
(44 reference statements)
3
28
0
Order By: Relevance
“…In HIGH OXPHOS AML (MOLM14) cells, we tested pharmacological agents well known to inhibit OXPHOS activities through the inhibition of mitochondrial protein synthesis (Tigecycline, TIG (40); Ethidium Bromide, (36,41)), Electron Transport Chain complex I (ETCI; Phenformin or Metformin (42); Rotenone) or Electron Transport Chain complex III (ETCIII; antimycin A or atovaquone (43)). As expected and shown by Bozhena Jhas et al (44), TIG-treated HIGH OXPHOS MOLM14 cells (Fig. 6C) exhibited a significantly decreased level of mitochondrial protein translation of ETCI and ETCIV (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In HIGH OXPHOS AML (MOLM14) cells, we tested pharmacological agents well known to inhibit OXPHOS activities through the inhibition of mitochondrial protein synthesis (Tigecycline, TIG (40); Ethidium Bromide, (36,41)), Electron Transport Chain complex I (ETCI; Phenformin or Metformin (42); Rotenone) or Electron Transport Chain complex III (ETCIII; antimycin A or atovaquone (43)). As expected and shown by Bozhena Jhas et al (44), TIG-treated HIGH OXPHOS MOLM14 cells (Fig. 6C) exhibited a significantly decreased level of mitochondrial protein translation of ETCI and ETCIV (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Skrtić et al (2011) found that TIG has selective toxicity on leukemia cells, especially leukemia stem and progenitor cells in vitro and in vivo , and this cell cytotoxicity of TIG depends on the intact respiratory chain. However, TIG-resistant cancer cells show more resistance to hypoxia with an upregulated hypoxia-inducible factor 1α (HIF-1α) level from defective oxidative phosphorylation (Jhas et al, 2013). Using the haplo-insufficiency profiling screen, a well-validated, automated and high-throughput chemogenomic assay platform developed in yeast, mitochondrial protein synthesis has been identified as the mechanism of TIG-induced lethality.…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%
“…The IC50 of metformin was reduced in all cells with silenced AKT isoforms compared to control cells as ascertained by RTCA, and it was significant in AKT1silenced cells compared to shCT control cells ( Figure 4C). Tigecycline was then tested as a highly selective inhibitor of the mitochondrial respiratory chain without disrupting the mTOR pathway (Jhas et al, 2013;Skrtic et al, 2011). Cells adapted to AKT1 silencing exhibited the strongest increase in sensitivity to tigecycline (Figure 4D), although it did not reach statistical significance ( Figure 4E).…”
Section: Figure 2 the Mitochondrial Proteome Is Significantly Alterementioning
confidence: 99%
“…However, in many instances it is difficult to ascribe the contribution of each isoform to the biology of the cancer cell. While AKT1 is pro-tumorigenic in lung cancer and ErbB2 positive breast cancer (Hollander et al, 2011;Hutchinson et al, 2004;Ju et al, 2007;Linnerth-Petrik et al, 2014;Maroulakou et al, 2007), its silencing is pro-tumorigenic in prostate and other types of breast cancer (Irie et al, 2005;Liu et al, 2006;Virtakoivu et al, 2012;Yoeli-Lerner et al, 2005). In murine breast cancer models, AKT2 abrogation suppresses cell migration, and its expression stimulates motility and invasion in prostate cancer cells in vitro, and in breast and ovarian cancer in vivo.…”
Section: Introductionmentioning
confidence: 99%